LINC01006 regulates the proliferation, migration and invasion of hepatocellular carcinoma cells through regulating miR-433-3p/CBX3 axis - Yaobo Song (Elsevier, 2021)
Introduction and objectives: LINC01006 has been verified to be correlated with several cancer types, whereas its biological function in hepatocellular carcinoma (HCC) is still elusive. This study aimed to elucidate the specific regulatory mechanism of LINC01006 in the tumorigenesis of HCC. Materials and methods: The expression of LINC01006, miR-433-3p and CBX3 in HCC tissues and cells was assessed by qRT-PCR or Western blot. MTT, wound-healing, and transwell assays were used to evaluate the effects of LINC01006 on cell viability, migration, and invasion in vitro. A mouse xenograft model was established for in vivo assays. The relations among LINC01006, miR-433-3p, and CBX3 were analyzed by MS2-RNA immunoprecipitation (RIP) and Dual-luciferase reporter (DLR) assays. Results: The expression of LINC01006 was up-regulated in HCC tissues and cells. LINC01006 knockdown inhibited the viability, wound healing rate, and invasive cell number of HeP3B and SK-HeP-1 cells, and decreased the tumor volume and weight in a mouse xenograft model. MiR-433-3p was a target of LINC01006, and LINC01006 overexpression inhibited the viability, wound healing rate, and invasive cell number of HeP3B and SK-HeP-1 cells. In addition, CBX3 was a target of miR-433-3p, which was negatively regulated by miR-433-3p. CBX3 overexpression and miR-433-3p inhibition reversed the inhibiting effects of LINC01006 knockdown on the viability, migration, and invasion of HeP3B cells. Conclusions: Silencing of LINC01006 inhibited the viability, migration, and invasion of HCC cells through regulating miR-433-3p/CBX3 axis.